Trace-element abundances in the shallow lithospheric mantle of the North Atlantic Craton margin: Implications for melting and metasomatism beneath Northern Scotland - Hughes, HSR; McDonald, I; Faithfull, JW; Upton, BGJ; Downes, H (Mineralogical Magazine, 2015)
This is the final version of the article. Available from Mineralogical Society via the DOI in this record. Bulk rock geochemistry and major- and trace-element compositions of clinopyroxene have been determined for three suites of peridotitic mantle xenoliths from the North Atlantic Craton (NAC) in northern Scotland, to establish the magmatic and metasomatic history of subcontinental lithospheric mantle (SCLM) below this region. Spinel lherzolites from the southernmost locality (Streap Com'laidh) have non-NAC mantle compositions, while the two northern xenolith suites (Loch Roag and Rinibar) are derived from the thinned NAC marginal keel. Clinopyroxene compositions have characteristic trace-element signatures which show both 'primary' and 'metasomatic' origins. We use Zr and Hf abundances to identify ancient cryptic refertilization in 'primary' clinopyroxenes. We suggest that Loch Roag and Rinibar peridotite xenoliths represent an ancient Archaean-Palaeoproterozoic SCLM with original depleted cratonic signatures which were overprinted by metasomatism around the time of intrusion of the Scourie Dyke Swarm (∼2.4 Ga). This SCLM keel was preserved during Caledonian orogenesis, although some addition of material and/or metasomatism probably also occurred, as recorded by Rinibar xenoliths. Rinibar and Streap xenoliths were entrained in Permo-Carboniferous magmas and thus were isolated from the SCLM ∼200 Ma before Loch Roag xenoliths (in an Eocene dyke). Crucially, despite their geographical location, lithospheric mantle peridotite samples from Loch Roag show no evidence of recent melting or refertilization during the Palaeogene opening of the Atlantic. H.S.R. Hughes was funded by the Natural Environment Research Council (NERC) studentship NE/J50029X/1